The Role of Insurance Agents in Building Public Trust in Sharia Education Insurance at Bank BSI Medan City in the Digital Era - Ahmad Ibnu Harahap; Waizul Qarni; Khairina Tambunan (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to determine the role of insurance agents in building public trust in Islamic education insurance in the digital era, to analyze the strategies used by insurance agents to increase the trust of prospective customers in Islamic education insurance products and analyze the challenges faced by insurance agents in reaching the public and building trust through digital media. This study is a qualitative study with a SWOT approach to identify weaknesses, strengths, opportunities and threats. The results of the study indicate that the role of insurance agents in building public trust in Islamic education insurance in the digital era includes insurance agents as credible information liaisons, agent integrity and professionalism as determinants of trust, the use of digital technology to reach and educate customers and an emphasis on Islamic principles as the main selling point. The strategies used by insurance agents to increase the trust of prospective customers in Islamic education insurance products are a personal approach as an initial strategy to build trust, identification of customer needs as the basis for product offerings, ongoing communication to maintain and strengthen trust, the role of agents as trusted advisors and trust as the key to success. The challenges faced by insurance agents in reaching the public and building trust through digital media are high competition for information in digital media, public doubts about online transactions, low financial literacy and product understanding, limited reach due to social media algorithms, as well as negative stigma and the risk of fraud.